TINJAUAN YURIDIS PELAKSANAAN PEMBIMBINGAN TERHADAP KLIEN ANAK PROGRAM PEMBEBASAN BERSYARAT DI BALAI PEMASYARAKATAN KELAS I SURABAYA - Indriyani Aditya Setyaningrum (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2021)
Getting guidance is the right of all clients at Balai Pemayarakatan, including children clients. Parole is granted with various conditions given. These rights are given by considering the needs of prisoners and correctional students (andikpas). After obtaining parole (PB), Leaving Towards Free (CMB) or Conditional Leave (CB), the prisoner's status changes to become adult clients and correctional students turn into child clients, because they are under the guidance of the Community Advisor at the Correctional Center.Definition of Community Guidance Based on Law Number 3 of 1997 concerning Juvenile Justice Article 1 number 11 and Law Number 11 of 2012 concerning the Criminal Justice System for Children Article 1 point 13 explains that Community Guidance is a functional position in community law enforcement who carries out tasks in Correctional Center with duties and functions to carry out litmas (social research), guidance, supervision, and assistance to correctional clients both inside and outside the criminal justice process.The form of guidance provided can include spiritual guidance, attitude education, as well as providing guidance and counseling programs that can be carried out individually or in groups. The form of guidance provided to the Client is based on the present and future problems and needs of the Client, which is harmonized with family life and the community environment.